CARDIOGENIC SHOCK: CLINIC, EMERGENCY CARE (Western European Journal of Medicine and Medical Science, 2024)
Cardiogenic shock is a life-threatening condition of critical organ hypoperfusion (lack of blood supply), due to a decrease in cardiac output, which is characterized by: 1. A decrease in SBP